Integration of Reward, Innovative Behavior, Job Satisfaction on Job Performance for middle manager level employees - Laij Victor Effendi; Wirawan Endro Dwi Radianto (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to investigate the relationship between reward and employee performance, which is still inconsistent. We also investigate innovative behavior and job satisfaction as variables that mediate the effect of rewards on performance. The research method used is survey method by sending questionnaires to employees at the managerial level. We used multivariate analysis as an analytical tool for this study. The result of this study is that rewards affect performance, innovative behavior, and job satisfaction. Innovative behavior and job satisfaction affect performance. Innovative behavior and job satisfaction partially mediate the relationship between reward and performance. We found that if employees are satisfied with the rewards received, it will directly encourage employee performance, and there is no need for a mediator to improve performance.